2020
DOI: 10.3892/mmr.2020.10997
|View full text |Cite
|
Sign up to set email alerts
|

Gli3 is a novel downstream target of miR‑200a with an anti‑fibrotic role for progression of liver fibrosis in�vivo and in�vitro

Abstract: GLI family zinc finger 3 (Gli3), as the upstream transcriptional activator of hedgehog signaling, has previously been demonstrated to participate in the process of liver fibrosis. The present study aimed to investigate the potential functions of microRNA (miR)-200a and Gli3 in the progression of liver fibrosis. The expression levels of miR-200a and Gli3 in cells and tissues were determined by PCR and western blotting; the interaction of Gli3 and miR-200a was evaluated by bioinformatics analysis and dual-lucife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In addition, the level of IL-4 in the Lenti-miR-200a group decreased significantly in the 4th and 8th weeks of infection, suggesting that miR-200a could inhibit the development of liver fibrosis to some extent. It has been reported that increasing expression of miR-200a attenuates HSC proliferation while knocking down miR-200a-promoted HSC proliferation [ 21 ]. And consistent with our result, it was reported that miR-200a upregulation contributed to the suppression of activated HSCs, leading to a reduction in cell proliferation, ECM production and α-SMA expression [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the level of IL-4 in the Lenti-miR-200a group decreased significantly in the 4th and 8th weeks of infection, suggesting that miR-200a could inhibit the development of liver fibrosis to some extent. It has been reported that increasing expression of miR-200a attenuates HSC proliferation while knocking down miR-200a-promoted HSC proliferation [ 21 ]. And consistent with our result, it was reported that miR-200a upregulation contributed to the suppression of activated HSCs, leading to a reduction in cell proliferation, ECM production and α-SMA expression [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%